Emerging Role of Lymphocyte Antigen-6 Family of Genes in Cancer and Immune Cells - Upadhyay, Geeta (Frontiers in Immunology, 2019)
Stem Cell Antigen-1 (Sca-1/Ly6A) was the first identified member of the Lymphocyte antigen-6 (Ly6) gene family. Sca-1 serves as a marker of cancer stem cells and tissue-resident stem cells in mice. The Sca-1 gene is located on mouse chromosome 15. While a direct homologue of Sca-1 in humans is missing, human chromosome 8 - the syntenic region to mouse chromosome 15 - harbors several genes containing the characteristic domain known as LU domain. The function of the LU domain in human LY6 gene family is not yet defined. The LY6 gene family proteins are present on human chromosome 6. 8, 11 and 19. The most interesting of these genes are located on chromosome 8q24.3, a frequently amplified locus in human cancer. Human LY6 genes represent novel biomarkers for poor cancer prognosis and are required for cancer progression in addition to playing an important role in immune escape. Although the mechanism associated with these phenotypes is not yet clear, it is timely to review the current literature in order to address the critical need for future advancements in this field. This review will summarize recent findings which describe the role of human LY6 genes - LY6D, LY6E, LY6H, LY6K, PSCA, LYPD2, SLURP1, GML, GPIHBP1 and LYNX1; and their orthologues in mice at chromosome 15.